Solitons Solutions of the Complex Ginzburg-Landau Equation with Saturation Term Using Painleve Truncated Approach - Kamdoum-Tamo, P.H.; Kenfack-Jiotsa, A.; Kofane, T.C. (Journal of Applied Nonlinear Dynamics, 2026)
Considering the pulse ansatz, we derive different classes of the modified complex Ginzburg-Landau (MCGL) equation and we use the Painleve truncated approach to construct the solitons solutions . We then present the importance of the saturation term. The solutions obtained by the combined methods are asymmetric- dark and bright solitons. Numerical simulations are performed to show how the wave propagates. The shape of solutions can be well controlled by adjusting the parameters of the system.